Responsabilidad social corporativa en las entidades financieras españolas (2020)
This research aims to analyze the responsible practices developed by financial institutions, as related to corporate social responsibility (CSR), and determine if the degree of intensity in the execution of these responsible policies is related to the size or solvency of these institutions.   On the basis of a positivist approach and using the main measurement standards of CSR, the validation of some hypotheses based on a previous empirical analysis was carried out. A sample of financial institutions was used to understand the degree of commitment of large financial companies to their stakeholders, the environment, and society in general.